Problematika Hukum Kewenangan Pejabat Pengawas Lingkungan Hidup Dalam Penegakan Hukum Lingkungan Di Bidang Pertambangan - Wongkar, Vonny Anneke; Robert Nicolas Warong; Cobi Elisabeth M. Mamahit (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Mining activities are closely related to society and the environment because every mining business must maintain the continuity of the carrying capacity and capacity of the environment. Environmental supervisory officials are obliged to supervise compliance with the person responsible for business and/or activities carried out based on statutory regulations in the field of environmental protection and management. This research aims to determine the authority of environmental supervisory officials in enforcing environmental law in the mining sector. This research uses normative research methods with a statutory approach, conceptual approach and case approach. Apart from that, empirical research methods are also used so that we can get results regarding the authority of environmental supervisory officials in enforcing laws in the mining sector. The process of enforcing environmental law in the mining sector must be implemented from the stage of the process of fulfilling environmental permits and AMDAL studies, then planning, implementation and supervision, both at the exploration, production and post-mining stages. Enforcement of environmental law carried out by environmental supervisory officials in the mining sector signals to business actors to address the recovery of the social and economic environment as a result of a mining business activity located in the local government area. Environmental supervisory officials in law enforcement in the mining sector must carry out their duties and obligations in accordance with applicable laws.